2020
DOI: 10.1097/adm.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Low Barrier Tele-Buprenorphine in the Time of COVID-19: A Case Report

Abstract: Background: To reduce the spread of coronavirus disease 2019 (COVID-19), many substance use disorder treatment programs have transitioned to telemedicine. Emergency regulatory changes allow buprenorphine initiation without an in-person visit. We describe the use of videoconferencing for buprenorphine initiation combined with street outreach to engage 2 patients experiencing homelessness with severe opioid use disorder (OUD). Case Presentation: Patient 1 was a 30-year-old man with severe OUD who had relapsed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 11 publications
1
86
1
Order By: Relevance
“…In-home initiation of buprenorphine is a routine in some Western countries ( Poloméni and Schwan, 2014 ) and newer long-acting injectable formulations of buprenorphine may be preferred. Buprenorphine initiation via telemedicine is legally possible in the U.S and has been successfully reported in a case report study ( Harris et al, 2020 ). A retrospective two years study found no difference between telemedicine and face-to-face buprenorphine medication-assisted treatment programs ( Zheng et al, 2017 ).…”
Section: Results and Observationsmentioning
confidence: 99%
“…In-home initiation of buprenorphine is a routine in some Western countries ( Poloméni and Schwan, 2014 ) and newer long-acting injectable formulations of buprenorphine may be preferred. Buprenorphine initiation via telemedicine is legally possible in the U.S and has been successfully reported in a case report study ( Harris et al, 2020 ). A retrospective two years study found no difference between telemedicine and face-to-face buprenorphine medication-assisted treatment programs ( Zheng et al, 2017 ).…”
Section: Results and Observationsmentioning
confidence: 99%
“…Sexual Health Care Clinics and SSPs provided examples on how to connect patients with providers during COVID-19 via telehealth [12,13], and a recent opinion paper demonstrated the utility of telehealth in preventing disruption of care for people with OUD and co-occurring mental health disorders during COVID-19 [14]. With the development of TeleMOUD, we aimed to mitigate disruptions in care by serving patients with OUD who could not receive in person care within a hospital or clinic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Medication Assisted Treatment in the Criminal Justice System: Brief Guidance to the States. 2019 ( Substance Abuse and Mental Health Services Administration, 2019b ) California Health Care Foundation Medication-Assisted Treatment in County Criminal Justice Settings Project ( California Health Care Foundation, 2018 ) American Society of Addiction Medicine Treatment in Correctional Settings Toolkit ( American Society of Addiction Medicine, 2019b ) Principles of Drug Abuse Treatment for Criminal Justice Populations-A Research-Based Guide ( National Institute on Drug Abuse, 2014a ) Protocol for Consent to Treatment with Medications for Opioid Use Disorder in Correctional Facilities ( Massachusetts Bureau of Substance Addiction Services, 2019 ) Expanding access to MOUD treatment through telemedicine, interim buprenorphine or methadone, or medication units Medication units: electronic-Code of Federal Regulations - 8.11 ( Office of the Federal Register and Government Publishing Office, 2019b ; Substance Abuse and Mental Health Services Administration, 2015b ) Interim methadone: electronic-Code of Federal Regulations – 8.11 ( Newman, 2014 ; Office of the Federal Register and Government Publishing Office, 2019a ; Schwartz et al, 2006 ) Interim buprenorphine ( Office of the Federal Register and Government Publishing Office, 2019b ; Sigmon et al, 2016 ) Low Barrier Tele-Buprenorphine ( Harris et al, 2020 ) MOUD Bridge Programs ( Snow et al, 2019 ) San Francisco Street Medicine Team ( Carter et al, 2019 ) Telemedicine&Prescribing Buprenorphine for the Treatment of Opioid Use Disorder ( U.S. Department of Health and Human Services, 2018 ) Project “Support for Hospital Opioid Use Treatment” Webinar on Telemedicine and MOUD Treatment ( Project SHOUT and California Health Care Foundation, 2018 ) Interventions to Link to MOUD (required) Linkage Programs (all relevant settings) Within (or initiated within) Service Settings Massachus...…”
Section: Methodsmentioning
confidence: 99%
“…Expanding access to MOUD through telemedicine is especially salient as communities consider ORCCA strategies during the COVID-19 pandemic. Telemedicine models for buprenorphine treatment already existed ( U.S. Department of Health and Human Services, 2018 ), but guidance from the US Drug Enforcement Agency, SAMHSA, the Centers for Medicare & Medicaid Services, and state regulatory agencies changed rapidly ( Harris et al, 2020 ; Opioid Response Network, 2020 ; Providers Clinical Support System, 2020a ; Substance Abuse and Mental Health Services Administration, 2020c ) to allow greater flexibility of MOUD treatment via telemedicine during the pandemic. For example, the requirement for an in-person visit to begin MOUD was waived and dispensing of medications was allowed for longer periods of time.…”
Section: Methodsmentioning
confidence: 99%